DIGITAL TRANSFORMATION IN INDONESIAN SMES: DRIVERS, BARRIERS, AND PERFORMANCE OUTCOMES - Aripin, Zaenal; Susanto, Bambang; Agusiady, Ricky (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: Indonesian small and medium enterprises (SMEs) constitute 99.9% of all businesses and contribute significantly to national GDP. However, digital adoption remains fragmented, with only 16% achieving advanced integration levels. The acceleration of digitalization post-pandemic has created unprecedented pressure on SMEs to transform digitally while simultaneously facing substantial resource, capability, and infrastructure constraints unique to emerging market contexts. Aims: This research investigates the multifaceted dynamics of digital transformation among Indonesian SMEs by examining: (1) primary drivers compelling digital adoption, (2) critical barriers impeding transformation efforts, and (3) performance outcomes associated with varying digital maturity levels. The study aims to develop a contextualized framework explaining digital transformation patterns in resource-constrained emerging market environments. Research Method: A mixed-methods design combined quantitative survey analysis of 287 SMEs across manufacturing, retail, services, and technology sectors with qualitative interviews of 15 business owners. Data collection spanned Jakarta, Surabaya, and Bandung during March-August 2024. Partial Least Squares Structural Equation Modeling (PLS-SEM) analyzed quantitative relationships while thematic analysis examined qualitative insights, enabling methodological triangulation. Results and Conclusion: Findings reveal customer expectations (β=0.42, p<0.001) as the strongest adoption driver, followed by competitive pressures (β=0.38) and supply chain requirements (β=0.31). Financial constraints emerged as the most cited barrier (73% of respondents), alongside skills gaps (67%) and technical complexity (58%). Digital maturity demonstrates significant positive correlations with operational efficiency improvements (r=0.48), market expansion (r=0.52), and revenue growth (r=0.56). Three distinct transformation archetypes emerged: Compliance-Driven adopters (38%), Strategic Adopters (29%), and Pioneering Transformers (33%). Contribution: This study extends Technology-Organization-Environment (TOE) framework application in emerging markets by demonstrating organizational learning capabilities as critical mediators between external pressures and adoption outcomes. The identification of distinct transformation archetypes reveals heterogeneity in organizational responses, contradicting institutional isomorphism predictions. Findings inform both SME strategic planning and policy interventions supporting inclusive digital economy development.